Editorial: Primary Locus Intervention: A novel approach to treating age-associated hormone insufficiency ||Free Paper|| - Richard F Walker (Dove Medical Press, 2008)
Richard F WalkerInternational Society for Applied Research in Aging (SARA)There is consensus among practitioners of age-management/longevity medicine that progressive failure of neuroendocrine function leads to hormone insufficiency, which underlies many of the maladaptive consequences of aging. Accordingly, one of the most commonly employed clinical interventions in aging is balanced hormone replacement therapy (HRT). This approach is often quite effective since many of the structural and functional consequence of aging result at least in part from inadequate endogenous hormone supply and/or imbalance of multiple hormone actions upon the body. However, while HRT is effective in opposing many of the more obvious degenerative effects of aging on body composition and function it does little to treat the pathophysiological factors underlying neuroendocrine decline. In fact, HRT may actually accelerate senescence of neuroendocrine elements within the brain and pituitary gland.